Sit to stand activity during stroke rehabilitation. Issue 8 (17th November 2017) - Kerr, Andy; Dawson, Jesse; Robertson, Chris; Rowe, Philip; Quinn, Terence J.
Abstract: Objectives: The sit to stand (STS) movement is key to independence and commonly affected by stroke. Repetitive practice is likely to improve STS ability during rehabilitation, however current practice levels are unknown. The objective of this study was simply to count the number of STS movements performed during the rehabilitation period of stroke patients using a physical activity monitor (PAM) and test whether being observed altered outcome. Methods: Participants were medically stable patients referred for rehabilitation following stroke. Participants were randomly allocated to either wear or not wear the PAM for 14 days. STS ability and general mobility were recorded before and after. Results: Sixty-one patients was recruited; aged 68.4 ± 13.15 years, weight 77.12 ± 22.73 Kg, Height 1.67 ± 0.1 m, within 9 ± 9 days of their stroke and an NIHSS score of 6.4 ± 3.3. The monitored group ( n  = 38) performed 25.00 ± 17.24 daily STS movements. Those requiring assistance achieved 14.29 ± 16.10 per day while those independent in the movement achieved 34.10 ± 12.44. There was an overall improvement in mobility ( p  = 0.002) but not STS performance ( p  = 0.053) neither outcome was affected by group allocation ( p  = 0.158). Cognition and mobility at baseline explained around 50% of daily STS variability. Discussion: Low levels of STS activity were recorded during the rehabilitation period of stroke patient. The mean daily STS activity was lower than reports for frail older people receiving rehabilitation, and substantially below levels recorded by community living older adults. STS repetitions may represent general physical activity and these low levels support previous reports of sedentary behavior during rehabilitation.